2014
DOI: 10.1038/jes.2014.85
|View full text |Cite
|
Sign up to set email alerts
|

Transmission through air as a possible route of exposure for MRSA

Abstract: Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) is highly prevalent in pigs and veal calves. The environment and air in pig and veal calf barns is often contaminated with LA-MRSA, and can act as a transmission source for humans. This study explores exposure-response relationships between sequence type 398 (ST398) MRSA air exposure level and nasal ST398 MRSA carriage in people working and/or living on farms. Samples and data were used from three longitudinal field studies in pig and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 37 publications
4
65
0
Order By: Relevance
“…This is in contrast to a Finnish study [39], which observed that environmental biodiversity was associated with a higher generic diversity of skin gammaproteobacteria, presumably resulting from direct contact with environmental microbiota. Although there is some evidence that transmission of farm-related bacteria may take place through air—for example, in pig and veal calf farmers and their family members, nasal colonization by livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) occurs frequently [40]—we did not find evidence of zoonotic infections explaining the increased risk of CAP around poultry farms [9]. …”
Section: Discussionmentioning
confidence: 92%
“…This is in contrast to a Finnish study [39], which observed that environmental biodiversity was associated with a higher generic diversity of skin gammaproteobacteria, presumably resulting from direct contact with environmental microbiota. Although there is some evidence that transmission of farm-related bacteria may take place through air—for example, in pig and veal calf farmers and their family members, nasal colonization by livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) occurs frequently [40]—we did not find evidence of zoonotic infections explaining the increased risk of CAP around poultry farms [9]. …”
Section: Discussionmentioning
confidence: 92%
“…As S. aureus is transmitted via direct contact and through dust, it may be assumed that this organism is present throughout the entire farm and all pigs are exposed to this organism (17). Despite this general exposure, S. aureus was only detected in 65% of the animals.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that for pig farmers the most important determinants for becoming an MRSA carrier are the exposure to high amounts of MRSA in the air of the barn and the hours that are spent in the barn (17). That study did not find an association between MRSA persistence in farmers and the proportion of MRSA-positive animals on the farm.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, a specific clone of methicillin‐resistant Staphylococcus aureus (MRSA), referred to as livestock‐associated MRSA (LA‐MRSA) has emerged in livestock and people in direct contact with livestock, in particular, pigs and veal calves (Graveland et al, ; Voss et al, ). Although airborne transmission is a likely route of exposure in farmers (Bos et al, ), it is unclear whether LA‐MRSA is transmitted to nonfarming residents through the environment, for example, by air. In a large population survey, only 10 out of 2,492 Dutch adults carried LA‐MRSA, but carriers lived closer to a livestock farm than noncarriers, a difference that remained statistically significant after adjustment for farm animal contact (Zomer, Wielders, et al, ).…”
Section: Antimicrobial Resistancementioning
confidence: 99%